Awareness of and interest in oral pre-exposure prophylaxis (PrEP) for HIV prevention and interest in hypothetical forms of PrEP among people who inject drugs in rural West Virginia. Issue 6 (3rd June 2021) - Schneider, Kristin E.; White, Rebecca Hamilton; O'Rourke, Allison; Kilkenny, Michael E.; Perdue, Michelle; Sherman, Susan G.; Grieb, Suzanne M.; Allen, Sean T.
ABSTRACT: Injection drug use-associated HIV outbreaks have occurred in rural communities throughout the United States, which often have limited HIV prevention services for people who inject drugs (PWID). Pre-exposure prophylaxis (PrEP) is one tool that may help fill gaps in HIV prevention programing in rural settings. Oral PrEP has been approved for use, and new PrEP formulations are under development. Research is needed to better understand interest in oral and possible forthcoming PrEP formulations among PWID. We used survey data from 407 PWID in rural West Virginia. We asked if participants had heard of, taken, and were interested in taking PrEP, and about interest in several hypothetical forms of PrEP (arm injections, abdomen injections, implants, intravenous infusions). We estimated the prevalence of interest in each formulation and assessed correlates using Chi-squared tests. A minority had heard of oral PrEP (32.6%), and few had used it (3.7%). Many were interested in using oral PrEP (58.3%). Half were interested in arm injections (55.7%). Common correlates of interest across PrEP formulations were sexual minority status, comfort talking to a doctor about sex, sex work, and sharing injection equipment. Oral and injectable PrEP have the potential to fill HIV prevention gaps for rural PWID.